2018
DOI: 10.1093/asj/sjy199
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Smooth Surface Tissue Expander Breast Reconstruction

Abstract: STEs represent a safe and efficacious alternative to TTE breast reconstruction with at least equitable outcomes. Technique modification including tab fixation, ADM pocket control, postoperative bra support, and suture choice may contribute to observed favorable outcomes and are reviewed. Early results for infection control and explantation rate are encouraging and warrant comparative evaluation for potential superiority over TTEs in a prospective randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 44 publications
6
40
1
Order By: Relevance
“…Particularly considering the association of textured devices with BIA-ALCL, 18 it is prudent that studies investigate the safety and efficacy of surface texture on complication profiles and reconstructive outcomes. Recently, two studies described complication profiles of TEs specifically, although they did not compare the rate of malpositioning or evaluate time to final reconstruction 19,20 . Both studies reported overall smooth TE complication rates to be lower at 15.6% than textured TE (26.1% and 19.1%) and comparable to rates reported in this study.…”
Section: Discussionsupporting
confidence: 54%
“…Particularly considering the association of textured devices with BIA-ALCL, 18 it is prudent that studies investigate the safety and efficacy of surface texture on complication profiles and reconstructive outcomes. Recently, two studies described complication profiles of TEs specifically, although they did not compare the rate of malpositioning or evaluate time to final reconstruction 19,20 . Both studies reported overall smooth TE complication rates to be lower at 15.6% than textured TE (26.1% and 19.1%) and comparable to rates reported in this study.…”
Section: Discussionsupporting
confidence: 54%
“…The ability to drain periprosthetic fluid with ease not only permits treatment of postoperative seroma, but also allows aspirated fluid to be sent for culture. While the ability to use the integrated drain of the AlloX2 TE for periprosthetic washouts, and thus, successfully treating select patients with periprosthetic infections without surgical intervention have been previously reported, 7 , 18 , 19 the value of having knowledge of the microbiological makeup of the periprosthetic fluid in an asymptomatic patient became evident in a patient who went on to develop surgical site infection. Having knowledge of the presence of Actinomyces neuii permitted initiation of targeted antibiotic therapy without delay, thus, avoiding a trial with broad-spectrum antibiotics and permitting salvage of the device without surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of being able to identify the pathogen was also commented on by Fairchild et al, who following early detection and treatment of methicillin-resistant Staphylococcus aureus via intravenous and periprosthetic washout with vancomycin were able to salvage the TE without surgical intervention. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Additional studies are needed to analyze complications related to devices that incorporate novel tissue expansion technology (eg, smooth tissue expanders), 16 optimization of lower pole expansion, patient-directed tissue expansion, dual port expanders, or other technologies that have demonstrated benefits compared with the technology used in the present analysis. 3 However, these results demonstrate that the use of CPX4 Breast Tissue Expanders are a safe and efficacious option for women undergoing 2-stage, expander-to-implant based primary breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%